Effects of corporate transparency on tax avoidance: Evidence from Country-by-Country Reporting - Tijmen Tuinsma; Kristof De Witte; Petr Janský; Miroslav Palanský; Vitezslav Titl (Charles University in Prague, Institute of Economic Studies (IES), 2023)
Private Country-by-Country Reporting (CbCR) is a measure against tax avoidance by large multinationals, implemented throughout the EU in 2016. Multinational companies with an annual revenue over exteuro 750 million have been required to report their global activities on a country-by-country basis to tax authorities. Using this cutoff in a sharp regression discontinuity design, we find causal evidence for an increase in effective tax rates for affected companies, indicating an increase in tax compliance. We estimate the increase in effective tax rates at 5 to 6 percentage points locally. However, significant cross-sectional variation is present: the most aggressive multinationals with tax haven affiliates are at most moderately affected, while almost the full effect is concentrated in medium-aggressive firms. From a policy perspective, the results suggest that while CbCR was effective in combating some forms of tax avoidance, profit shifting opportunities in tax havens mostly negate this effect.
Keywords: F23; H25; H26; 330; corporate tax avoidance; tax havens; financial transparency